Effect of salt reduction, mixture of salt with animal fat, and salt particle sizes on instrumental texture, yield properties and sensory characteristics of burgers. - Coronado, Agataliz (2024)
This study aimed to investigate the impact of reduction of salt content (from 1.5 to 0.75%), the technique of mixing half of the salt content with animal fat, and the salt particle size on the instrumental texture, cooking losses, diameter reduction, overall liking, and sensory characteristics of burgers. The results showed that regardless of the types of micronized salt (MS<250 µm) incorporation (directly into the meat or the mixture of half of the MS with the meat and the other half with the fat), salt reduction decreased the salty perception and the instrumental hardness and chewiness. Thus, the mixture of MS with fat does not present sensory improvements nor overcome the texture effects of salt reduction. In a second experiment, the effect of different particle sizes (from <177 µm to 1 mm) was evaluated, where it was observed that salt with particle size <177 µm decreased the burgers’ hardness, cooking losses, and diameter reduction. The salt particle sizes did not cause sensory changes in the burgers, and in both experiments, the overall liking was greater than 7 points on the 9-point hedonic scale. Salt<177 µm could be a good option for reducing salt in burgers and possibly in other meat products.